Basil conservation affected by cropping season, harvest time and storage period - Silva, Franceli da; Santos, Ricardo Henrique Silva; Andrada, Nélio José de; Barbosa, Luiz Cláudio Almeida; Casali, Vicente Wagner Dias; Lima, Renato Ribeiro de; Passarinho, Ricardo Vaz de Melo (Pesquisa Agropecuaria Brasileira, 2005)
Fresh basil (Ocimum basilicum L.) is used in food, phytotherapic industry, and in traditional therapeutic, due to its essential oil content and composition. Nevertheless basil can not be kept for long periods after harvest and its quality can be reduced. This work aimed to assess the influence of the season and harvest time in the postharvest conservation of basil stored for different periods. Basil was harvested at 8 am and 4 pm both in August/1999 and January/2000. Cuttings were conditioned in PVC packages and stored for 3, 6, and 9 days. During storage, chlorophyll content, essential oil content and composition were determined as well as microbiological analyses were carried out. Harvest season and the days of storage influenced the final content of essential oil. There was a linear decrease in the content of essential oil, in the chlorophyll content and in the number of mold and yeast colonies during storage. There was no effect of cropping season or harvest hour on essential oil composition, but the eugenol and linalool content increased during storage. Coliforms were under 0.3 MPN g-1 and the number of Staphylococcus aureus was under 1.0x102 UFC g-1.